REVIEW ON THE ROAD TRAFFIC NOISE ASSESSMENT - ALINA PETROVICI; CLAUDIA TOMOZEI; FLORIN NEDEFF; OANA IRIMIA; MIRELA PANAINTE-LEHADUS (Journal of Engineering Studies and Research)
This paper presents a synthesis of current state of the assessment of road traffic noise in urban areas considering economic, social and legal aspects. Therefore, there were described several prediction methods of the urban traffic noise. These methods are useful in calculating the exposure of the population at noise levels which exceed the permissible limits. Mapping is one of the most common methods used for the assessment of noise. Whether it is industrial, airport, rail or road traffic noise, noise mapping provides accurate data needed later in developing action plans against noise. The road traffic noise assessments are performed periodically, and a representative picture of the noise in the analysed areas is obtained. Then, the action plans can be developed in order to reduce road traffic noise, where it is necessary.